Penthorum Chinense Pursh Extract Alleviates Aflatoxin B1-Induced Liver Injury and Oxidative Stress Through Mitochondrial Pathways in Broilers - Nabi, Fazul; Tao, Weilai; Ye, Ruiling; Li, Zhenzhen; Lu, Qin; Shang, Yangfei; Hu, Yu; Fang, Jiali; Bhutto, Zohaib Ahmed; Liu, Juan (Frontiers in Veterinary Science, 2022)
Aflatoxin is an important toxicant of the fungal origin and poses a threat to the poultry industry. This study was designed to reveal the underlying mechanism and protective methods against aflatoxin B1 (AFB1)-induced liver injury, oxidative stress, and apoptosis using a Chinese folk medicine, Penthorum chinense Pursh extract (PCPE), in broilers. A total of 164 (day-old) broilers were equally allocated to the control, AFB1 (3 mg/kg feed), positive drug (Yin-Chen-Hao Tang extract, 10 mL/kg feed), PCPE (2 g PCPE/kg), and PCPE low, medium, and high dose groups (1 g, 2 g, 3 g PCPE/kg feed, respectively). When compared with the control group, AFB1 significantly decreased the growth performance and serum immunoglobulin level, altered normal serum biochemical parameters and antioxidant activities, and induced histopathological lesions in the liver. Additionally, AFB1 significantly up-regulated the mRNA expression levels of apoptosis-related genes such as Bax, Bak, caspase-9, caspase-3, and p53, whereas it down-regulated the expression levels of BCL2 in the liver of broilers. The supplementation of different doses of PCPE to AFB1-affected birds significantly eased AFB1 negative effects by improving growth performance, immunoglobulin level, and oxidative capacity, and reversed oxidative stress and pathological lesions in liver. Furthermore, supplementation of PCPE to the AFB1 group reversed apoptosis by significantly down-regulating the mRNA expression levels of Bax, Bak, caspase-9, caspase-3, and p53 and up-regulating the expression levels of BCL2 in the liver of broilers. Based on these results, we conclude that supplementation of PCPE is protective and safe against oxidative stress, is anti-apoptotic, and reverses the liver damage caused by AFB1 in broilers.